Personality Assessment of the Elite Women Cricket Players: The Influence of Personality on Elite Women Cricket Players (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Cricket was first played in southern England in the 16th century. By the end of the 18th century, it had developed into the national sport of England. The expansion of the British empire led to cricket being played overseas and by the mid-19th century the first international matches were being held. The ICC, the game's governing body, has 10 full members. The game is most popular in Australia, England, the Indian subcontinent, the west indies and southern Africa.